К вопросу о непрерывности многозначных отображений - Остапенко, В.В. (Український математичний журнал, 1995)
Розглядається питання напівнеперервності зверху і знизу об'єднання та перерізу родини многозначних відображень. Одержані нові умови напівнеперервності знизу перерізу родини напівнеперервних знизу відображень. We study the problem of the upper and lower semicontinuity of the union and intersection for a family of many-valued mappings. We establish new conditions of lower semicontinuity for the intersection of a family of lower semicontinuous mappings.